PENGARUH KUALITAS LAYANAN DAN KINERJA KARYAWAN TERHADAP KEPUASAN NASABAH KOPERASI PONDOK PESANTREN MAMBA’UL MUBBASYIRIN SHIDDIQIYYAH BOJONEGORO - Agung, Dwi; Martono, Trisno; Ak, Bandi (Jurnal Pendidikan Insan Mandiri, 2015)
Cooperation are expected to be the cornerstone of the nation's economy. Cooperation as one service company will face stiff competition segment of micro and small. First services company to a financial institution, should really take advantage of quality services to excel in competition. Efforts focused on customer satisfaction development programs, through the quality and performance of employees. The purpose of this research is: 1) to analyze the influence of the quality of the service, to customer satisfaction cooperation Boarding School Mamba'ul Mubbasyirin Shiddiqiyyah Bojonegoro, 2) analyze the effect of the Employee Performance Customer Satisfaction Cooperation Boarding School Mamba'ul Mubbasyirin Shiddiqiyyah Bojonegoro, and 3) to analyze the influence quality of Service and Employee Performance together on Customer Satisfaction Cooperation Boarding School Mamba'ul Mubbasyirin Shiddiqiyyah Bojonegoro. The method used is an ex post facto quantitative descriptive approach. The population in this study is a cooperation customers Boarding School Mamba'ul Mubbasyirin Shiddiqiyyah Bojonegoro, amounting to 400 people. Sample was 189 people, which is determined by using the Proportionate Stratified Random Sampling technique is by way of lottery. Data was collected through observation and the questionnaire. Data were analyzed using multiple regression analysis. The results are: 1) The quality of individual services affect customer satisfaction Cooperation Boarding School Mamba'ul Mubbasyirin Shiddiqiyyah Bojonegoro, 2) The performance of individual employees affect customer satisfaction cooperation Boarding School Mamba'ul Mubbasyirin Shiddiqiyyah Bojonegoro, 3) Quality of service and performance of employees jointly affect customer satisfaction cooperation Boarding School Mamba'ul Mubbasyirin Shiddiqiyyah Bojonegoro. Keywords: quality of service, employee performance, customer satisfaction